KAJIAN ANALISIS KUALITAS UDARA DI KAWASAN MIGAS : STUDI KASUS (TUBAN DAN GRESIK) JAWA TIMUR - A S Patimah; S H Murti; A Prasetya (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
Activities generated from the Central Processing Area (CPA) in Tuban and Gresik, East Java, produce exhaust gases that have the potential to have an impact on the surrounding environment. The objectives of the study (1) are to determine the ambient air produced by the oil and gas industry production unit (2) to determine the odor intensity produced by the oil and gas industry production unit (3) to determine the noise intensity generated by the oil and gas industry production unit. This research was conducted in semester II 2018. Data analysis methods and air sampling were carried out using a Gas Sampler and measurement of TSP (Total Suspended Solid) parameters with HVS (High Volume Sampler), the air sample obtained was then tested according to the method that refers to applicable regulations in accordance with environmental permits. The results of the laboratory analysis are then compared with the applicable quality standards. The parameters studied are: ambient air SO2, NOx, CO, O3, TSP, odors of NH3, CH2SH, H2S, (CH2)2S, C6H5CHCH2 and noise levels conducted in semester II (quarters 3 and 4) in 2018. Parameter analysis results ambient air in the 3rd and 4th quarters, the highest SO2 at Mudi PAD B 3.8 g/Nm3, NOx and NH3 in the 3rd and 4th quarters were constant, the highest CO was at the Mudi PAD A location 377.9 g/Nm3 in the 3rd quarter and increased in 4th quarter 389.4 g/Nm3. Odor parameters in the third and fourth quarters, namely NH3 from all locations tended to be constant <0.01 ppm, H2S fluctuated in the third quarter and decreased in the fourth quarter <0.01 ppm, C6H5CHCH2 <0.05, still below the quality standard of 0.1 ppm. Noise parameters in the 3rd and 4th quarters in Suci Village are 44.7 dB, GKB Housing 46 dB, Klangonan Village 49 dB, Mudi PAD C 48 dB, Mudi PAD A 54.2 dB, Mudi PAD B 53.8 dB in the third quarter. below the quality standard of 58 dB and 73.0 dB. Based on the results of the comparative analysis of air, odor and noise around Tuban and Gresik in accordance with the quality standards required by the East Java Governor Regulation No. 10 of 2009. The quality of noise and odors is in accordance with the quality standards required by the Decree of the Minister of the Environment No. 46 and no 50 of 1996. However, there are several standard parameters that are still fluctuating, namely H2SKegiatan yang dihasilkan dari Central Processing Area (CPA) di Tuban dan Gresik Jawa Timur, menghasilkan gas buang berpotensi menimbulkan dampak terhadap lingkungan sekitar. Tujuan dari penelitian (1) mengetahui udara ambien yang dihasilkan unit produksi Industri migas (2) mengetahui intensitas kebauan yang dihasilkan unit produksi Industri migas (3) mengetahui intensitas kebisingan yang dihasilkan unit produksi Industri migas. Penelitian ini dilakukan pada smester II tahun 2018. Metode analisis data dan pengambilan sampel udara dilakukan dengan menggunakan Gas Sampler dan pengukuran parameter TSP (Total Suspended Solid) dengan HVS (High Volume Sampler), sampel udara yang diperoleh kemudian dilakukan pengujian sesuai metode yang mengacu pada peraturan yang berlaku sesuai izin lingkungan. Data hasil analisis labolatorium selanjutnya dibandingkan dengan baku mutu yang berlaku. Parameter yang dikaji yaitu : udara ambien SO2, NOx, CO, O3, TSP, kebauan NH3, CH2SH, H2S, (CH2)2S, C6H5CHCH2 dan tingkat kebisingan yang dilakukan pada smester II (quartal 3 dan 4) tahun 2018. Hasil analisis parameter udara ambien di quartal 3 dan 4 yaitu SO2 tertinggi di Mudi PAD B 3,8 ?g/Nm3, NOx dan NH3 di quartal 3 dan 4 konstan, CO tertinggi di lokasi Mudi PAD A 377,9 ?g/Nm3 quartal 3 dan mengalami kenaikan di quartal 4 389,4 ?g/Nm3. Parameter kebauan quartal 3 dan 4 yaitu NH3 dari semua lokasi cenderung konstan <0,01 ppm, H2S fluktuatif di quartal 3 dan mengalami penuruna di quartal 4 < 0,01 ppm, C6H5CHCH2 <0,05 masih dibawah baku mutu 0,1 ppm. Parameter kebisingan di quartal 3 dan 4 di desa Suci 44,7 dB, Perumahan GKB 46 dB, Desa Klangonan 49 dB, Mudi PAD C 48 dB, Mudi PAD A 54,2 dB, Mudi PAD B 53,8 dB pada quartal 3 masih dibawah baku mutu 58 dB dan 73,0 dB. Berdasarkan hasil perbandingan analisis udara, kebauan dan kebisingan di sekitar Tuban dan Gresik sesuai dengan baku mutu yang dipersyaratkan dalam Peraturan Gubernur Jawa Timur Nomor 10 tahun 2009. Kualitas kebisingan dan kebauan telah sesuai dengan baku mutu yang dipersyaratkan dalam Keputusan Menteri Lingkungan Hidup No. 46 dan no 50 tahun 1996. Namun ada beberapa standar parameter yang masih fluktuatif yaitu H2S